Movement Disorder in Ataxia-Telangiectasia: Treatment With Amantadine Sulfate. (February 2013) - Nissenkorn, Andreea; Hassin-Baer, Sharon; Lerman, Sheera F.; Levi, Yonit Banet; Tzadok, Michal; Ben-Zeev, Bruria
Ataxia-telangiectasia is a cerebellar neurodegenerative disorder presenting with ataxia, chorea, myoclonus, and bradykinesia. Literature on treatment of movement disorders is scarce. We treated 17 children (aged 11.2 ± 3.9 years) for 8 weeks with the dopaminergic and anti- N -methyl-d -aspartate (NMDA) agent amantadine sulfate 6.3 ± 0.87 mg/kg/d. Ataxia was assessed by using the International Cooperative Ataxia Scale, parkinsonism by the Unified Parkinson Disease Rating Scale, and chorea/myoclonus by the Abnormal Involuntary Movement Scale. Responders were considered those patients who had at least 20% improvement in the summation of the 3 scales. Overall, 76.5% of patients were responders, with a mean 29.3% improvement. Ataxia, involuntary movements, and parkinsonism improved significantly (25.3%, 32.5%, and 29.5%, respectively); ( P < .001, t test). Side effects were mild and transient, and they did not lead to drug discontinuation. Amantadine is a well-tolerated and effective treatment for motor symptoms in ataxia telangiectasia. Assessment of long-term effects and a double-blind study should follow.